STRATEGI PENERAPAN TRANSPORTATION DEMAND MANAGEMENT (TDM) DI KAWASAN INDUSTRI KRAKATAU KOTA CILEGON - Pradana, M. Fakhruriza; Bethary, Rindu Twidi; Agustianto, Irfan (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
The increasing of development and economic growth projections in the big cities such as Krakatau Industrial Area in Cilegon city, that would cause transportation problems such as traffic jam. The presence of transportation problem is need for appropriate handling, this handling does not put forward the problem solving instantly without regard to sustainability. Therefore, the policy development of urban transport infrastructure system in Indonesia using conventional approaches that are predict and provide should be abandoned and replaced with new approach that are predict and Prevent with the concept of Transportation Demand Management (TDM). The method used to choose the TDM strategy in Krakatau Industrial Area Cilegon city is the ranking method. Data was obtained by filling the questionnaire on 8 respondents who understand and can take transportation policy in Krakatau Industrial Area Cilegon city. Data processing by the help of Microsoft Excel program with the results Telework is the first rank as an appropriate strategy to be applied, and the program appropriate with the characteristics of Krakatau Industrial Area Cilegon city. Based on the results of the simulation analysis by using the methods of literature study on the implementation of telework, probability about 6.12% -23.66% of workers potentially do telework.